Optimalisasi Strategi Pemasaran Melalui Afiliasi E-Marketing Untuk Meningkatkan Konversi : Analisis Mendalam Terhadap Tren Industri Dan Praktik Terbaik - Amali, Amali; Hidayah, Aldy; Angela, Devani Nadia Vita Kusuma; Hamidah, Jilan (Jurnal Pelita Teknologi, 2023)
Affiliate e-marketing has become one of the most effective approaches in expanding reach and increasing sales in today's digital business environment. However, there are still obstacles in determining the right marketing strategy on the target market. This journal investigates optimization strategies to harness the potential of affiliate marketing in increasing conversions. Through an in-depth analysis of industry trends and best practices, this journal aims to provide valuable insights for digital marketing practitioners. The method used in this research is secondary data analysis where the research is qualitative. Here we see a great opportunity to be generated from an e-marketing affiliate business and will be a profitable business domain for affiliates in the future. The results of this study make sales in digital business can identify industry trends to optimize the use of affiliate marketing and achieve success in this increasingly digital business environment.